Acoustic Imaging with Metamaterial Luneburg Lenses. Issue 1 (December 2018) - Xie, Yangbo; Fu, Yangyang; Jia, Zhetao; Li, Junfei; Shen, Chen; Xu, Yadong; Chen, Huanyang; Cummer, Steven
Abstract The Luneburg lens is a spherically symmetrical gradient refractive index (GRIN) device with unique imaging properties. Its wide field-of-view (FoV) and minimal aberration have lead it to be successfully applied in microwave antennas. However, only limited realizations have been demonstrated in acoustics. Previously proposed acoustic Luneburg lenses are mostly limited to inherently two-dimensional designs at frequencies from 1 kHz to 7 kHz. In this paper, we apply a new design method for scalable and self-supporting metamaterials to demonstrate Luneburg lenses for airborne sound and ultrasonic waves. Two Luneburg lenses are fabricated: a 2.5D ultrasonic version for 40 kHz and a 3D version for 8 kHz sound. Imaging performance of the ultrasonic version is experimentally demonstrated.